Membrane Proteomic Insights into the Physiology and Taxonomy of an Oleaginous Green Microalga. Issue 1 (8th November 2016) - Garibay-Hernández, Adriana; Barkla, Bronwyn J.; Vera-Estrella, Rosario; Martinez, Alfredo; Pantoja, Omar
Abstract : RNA-Seq-based membrane proteomics provides insights into the biology of the oleaginous microalga Ettlia oleoabundans, allowing the identification of the novel proteins PSBS, MPH1, and RP2-CLC. Abstract: Ettlia   oleoabundans is a nonsequenced oleaginous green microalga. Despite the significant biotechnological interest in producing value-added compounds from the acyl lipids of this microalga, a basic understanding of the physiology and biochemistry of oleaginous microalgae is lacking, especially under nitrogen deprivation conditions known to trigger lipid accumulation. Using an RNA sequencing-based proteomics approach together with manual annotation, we are able to provide, to our knowledge, the first membrane proteome of an oleaginous microalga. This approach allowed the identification of novel proteins in E. oleoabundans, including two photoprotection-related proteins, Photosystem II Subunit S and Maintenance of Photosystem II under High Light1, which were considered exclusive to higher photosynthetic organisms, as well as Retinitis Pigmentosa Type 2-Clathrin Light Chain, a membrane protein with a novel domain architecture. Free-flow zonal electrophoresis of microalgal membranes coupled to liquid chromatography-tandem mass spectrometry proved to be a useful technique for determining the intracellular location of proteins of interest. Carbon-flow compartmentalization in E. oleoabundans was modeled using this information. Molecular phylogenetic analyses of protein markers and 18S ribosomal DNA support the reclassification of E. oleoabundans within the trebouxiophycean microalgae, rather than with the Chlorophyceae class, in which it is currently classified, indicating that it may not be closely related to the model green alga Chlamydomonas reinhardtii . A detailed survey of biological processes taking place in the membranes of nitrogen-deprived E. oleoabundans, including lipid metabolism, provides insights into the basic biology of this nonmodel organism.